Do Workers' Remittances Promote Economic Growth? - Gapen, Michael (IMF Working Papers; Working Paper, 2009)
Over the past decades, workers' remittances have grown to become one of the largest sources of financial flows to developing countries, often dwarfing other widely-studied sources such as private capital and official aid flows. While it is undeniable that remittances have poverty-alleviating and consumption-smoothing effects on recipient households, a key empirical question is whether they also serve to promote long-run economic growth. This study tackles this question and addresses the main shortcomings of previous empirical work, focusing on the appropriate measurement, and incorporating an instrument that is both correlated with remittances and would only be expected to affect growth through its effect on remittances. The results show that, at best, workers' remittances have no impact on economic growth.